Heat transfer and hydrodynamic characteristics of R-1336mzz(Z) as an alternative to R-245fa in a brazed plate heat exchanger with a distributor - Kim, Beomjun; Jeon, Yongseok; Lee, Dongchan (International Communications in Heat and Mass Transfer, 2025)
R-245fa has been widely used in organic Rankine cycles and high-temperature heat pumps. However, it must be phased out because of its high global warming potential. In this study, the heat transfer and hydrodynamic characteristics of R-1336mzz(Z) during evaporation were investigated as an alternative refrigerant to R-245fa in a brazed plate heat exchanger (BPHE) with a distributor at the inlet. Experiments were conducted by varying mass flux, saturation temperature, heat flux, and with partial and full evaporation. R-1336mzz(Z) exhibited approximately 28.4–35.0 % higher heat transfer coefficient than that of R-245fa because of a 73.54 % higher liquid-to-vapor density ratio, enhancing the heat transfer by the intensive interaction between the two phases. The frictional pressure drop of R-1336mzz(Z) was approximately 45.5–93.9 % higher than that of R-245fa, due to the higher density difference between the liquid and vapor phases, intensifying shear friction at the interface of the two phases. The distributor at the inlet of the BPHE increased the heat transfer coefficient by an average of 15.8 % through a uniform two-phase flow distribution. The existing correlations were insufficient for predicting the heat transfer coefficient and frictional pressure drop of the BPHE with a distributor; therefore, novel correlations were developed with reasonable accuracy.
Keywords: Brazed plate heat exchanger; Distributor; Frictional pressure drops; Heat transfer co-efficients; Heat-transfer characteristics; Hydrodynamic characteristics; Organics; R-1336mzz(Z); R-245fa; Two phase; Brazed plate heat exchanger; Distributor; Frictional pressure drop; Heat transfer coefficient; R-1336mzz(Z); R-245fa